Distinct roles of global cyclonic and anticyclonic eddies in regulating near-inertial internal waves in the ocean interior - Yuan, Man; Song, Zhuo; Jing, Zhao; Li, Zhuoran; Wu, Lixin (Frontiers in Marine Science, 2022)
In this study, we examine the regulation of wind-powered near-inertial internal waves (NIWs) in the ocean interior by mesoscale eddies, using an eddy-resolving global climate model. There is an enhancement (weakening) of NIW activity within anticyclonic (cyclonic) eddies from the surface boundary layer (SBL) base down to 4,000 m, associated with a decreased (increased) wave vertical scale. The influence of anticyclonic eddies on NIW activity is more pronounced than that of cyclonic eddies, suggesting that the net effect of mesoscale eddies is to intensify the NIWs in the ocean interior. The enhanced (weakened) NIW activity under the SBL in anticyclonic (cyclonic) eddies is ascribed to both horizontal convergence (divergence) of NIW energy flux under the SBL and increased (decreased) downward NIW energy flux from the SBL base. The former is only confined to a layer within several hundred meters under the SBL, whereas the latter becomes dominant in the deeper ocean.